2020
DOI: 10.14744/nci.2020.17136
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Relationship Between Polypharmacy and Anticholinergic Burden Scales

Abstract: OBJECTIVE: Polypharmacy and anticholinergic burden are the indicators for the evaluation of the quality of pharmacotherapy in older adults. The aim of this study was to consider which anticholinergic burden scales are more related with polypharmacy among older patients. METHODS: Four hundred and twenty older adults were evaluated retrospectively in this cross-sectional study. The patient’s demographic data, comorbidities, the drugs, and number of drugs were recorded. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In polypharmacy, anticholinergic load is associated with dysphagia [ 26 , 27 ], cognitive decline [ 51 ], and poor oral health [ 52 ]. Polypharmacy is a potentially high-risk factor for a high anticholinergic load [ 53 ]. The impact of polypharmacy should be considered when providing rehabilitation for dysphagia and individualized prescription optimization should be provided for correctable polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…In polypharmacy, anticholinergic load is associated with dysphagia [ 26 , 27 ], cognitive decline [ 51 ], and poor oral health [ 52 ]. Polypharmacy is a potentially high-risk factor for a high anticholinergic load [ 53 ]. The impact of polypharmacy should be considered when providing rehabilitation for dysphagia and individualized prescription optimization should be provided for correctable polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were asked to rate the ACB and the other tools against our tool, the IACT. The new AChB calculation system introduced with the IACT, was perceived useful as based on characteristics such as chemical structure, medication side-effects and textual information allowing to score newly added medications in the market, hence differentiating from other tools [ 19 ]. Minor issues highlighted were taken in consideration for amendment.…”
Section: Discussionmentioning
confidence: 99%
“…Lozano-Ortega et al [ 18 ] identified 16 scales, 6 of which were suitable for quantification of anticholinergic exposure. However, the use of these scales and others currently in use [ 19 ] is limited, because they do not use an updating system, and there are differences in which medications are included and the impact of dose.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…The anticholinergic burden of the individual medicines was assessed on a score of 0–3, according to their anticholinergic effects. A score of 0 represented no anticholinergic effect, a score of 1 signified possible, and scores of 2 and 3 implied definite anticholinergic effects [ 26 ]. The total anticholinergic burden in each patient was calculated.…”
Section: Methodsmentioning
confidence: 99%